Water-Processable P2-Na0.67Ni0.22Cu0.11Mn0.56Ti0.11O2 Cathode Material for Sodium Ion Batteries. Issue 2 (25th January 2019) - Mu, Linqin; Hou, Qingping; Yang, Zhenzhong; Zhang, Yan; Rahman, Muhammad Mominur; Kautz, David J.; Sun, Elaine; Du, Xi-Wen; Du, Yingge; Nordlund, Dennis; Lin, Feng
Abstract : Sodium ion batteries offer a low-cost, sustainable, and environment-friendly solution to large-scale electrochemical energy storage systems. Layered oxides represent a family of promising cathode materials with a potential to improve the energy and power densities while reducing the material cost of sodium ion batteries. However, due to the chemical and structural instability of layered oxides in an aqueous solution, the current battery electrode manufacturing requires expensive and hazardous organic solvents, which impedes the full benefit of the low-cost, sustainable, and eco-friendly advantages. We need an effective technology that empowers a cathode with water processable properties. In this study, we set a representative example, P2-Na0.67 Ni0.22 Cu0.11 Mn0.56 Ti0.11 O2, to explore its performance under water-processing conditions. This material achieves a discharge capacity of 180 mAh/g and a discharge energy of 544 Wh/kg at 22°C. The aging experiments indicate its superior stability against water, having negligible bulk structural or chemical changes. The surface sensitive soft X-ray absorption spectroscopy shows that the P2-Na0.67 Ni0.22 Cu0.11 Mn0.56 Ti0.11 O2 has stable surface chemistry in the aqueous solution. Moreover, the cells with water-processed cathodes delivered stable cycling performance with minor voltage decay, originating from the decreased cell impedance. Therefore, the present study sets a refined example to establish a low-cost, sustainable, and eco-friendly solution by developing water-processable electrode materials for sodium ion batteries.